Predictive Value of 3 Clinical Criteria for Sepsis (Quick Sequential Organ Failure Assessment, Systemic Inflammatory Response Syndrome, and National Early Warning Score) With Respect to Short-term Mortality in Allogeneic Hematopoietic Cell Transplant Recipients With Suspected Infections. (4th March 2020) - Lind, Margaret L; Phipps, Amanda I; Mooney, Stephen; Liu, Catherine; Fohner, Alison; Patel, Kevin; Ueda, Masumi; Pergam, Steven A
Abstract: Background: Sepsis disproportionately affects allogeneic hematopoietic cell transplant (HCT) recipients and is challenging to define. Clinical criteria that predict mortality and intensive care unit end-points in patients with suspected infections (SIs) are used in sepsis definitions, but their predictive value among immunocompromised populations is largely unknown. Here, we evaluate 3 criteria among allogeneic HCT recipients with SIs. Methods: We evaluated Systemic Inflammatory Response Syndrome (SIRS), quick Sequential Organ Failure Assessment (qSOFA), and National Early Warning Score (NEWS) in relation to short-term mortality among recipients transplanted between September 2010 and July 2017. We used cut-points of ≥ 2 for qSOFA/SIRS and ≥ 7 for NEWS and restricted to first SI per hospital encounter during patients' first 100 days posttransplant. Results: Of the 880 recipients who experienced ≥ 1 SI, 58 (6.6%) died within 28 days and 22 (2.5%) within 10 days of an SI. In relation to 10-day mortality, SIRS was the most sensitive (91.3% [95% confidence interval CI, 72.0%–98.9%]) but least specific (35.0% [95% CI, 32.6%–37.5%]), whereas qSOFA was the most specific (90.5% [95% CI, 88.9%–91.9%]) but least sensitive (47.8% [95% CI, 26.8%–69.4%]). NEWS was moderately sensitive (78.3% [95% CI, 56.3%–92.5%]) and specific (70.2% [95% CI, 67.8%–72.4%]). Conclusions: NEWS outperformed qSOFA and SIRS, but each criterion had low to moderate predictive accuracy, and the magnitude of the known limitations of qSOFA and SIRS was at least as large as in the general population. Our data suggest that population-specific criteria are needed for immunocompromised patients. Abstract : Sepsis disproportionately affects hematopoietic cell transplant (HCT) recipients, but clinical criteria currently recommended in sepsis detection have not been validated in these patients. We demonstrate the limited predictive value of commonly used clinical criteria among HCT recipients with suspected infections.